STUDI PERENCANAAN JEMBATAN CUMPLENG DENGAN METODE PRATEKAN DI KEC. SLAHUNG KABUPATEN PONOROGO - Adi Susanto; Yosef Cahyo; Sigit Winarto (Faculty of Engineering, Kadiri University, 2018)
In planning the Cumpleng Bridge in Slahung Sub-district, Ponorogo Regency with an overall span of 30 meters, the overall width of the bridge is 4.20 meters and the width of the pavement is 3.50 meters. Given the Cumpleng Bridge is one of several bridges in the Slahung District development project environment. This bridge has an important meaning as a link between Slahung Village and Galak Village, so it is expected to facilitate the flow of traffic and improve economic development and development in the area. In this planning study we use a prestressed method to calculate the calculation of the backrest and backrest poles, vehicle flooring, main girders and abutments / underbuildings. The results of this bridge planning include: planning the backrest, vehicle floor, main beam and transverse beam. Main beam using composite prestressed concrete post-tensioning method (post-tensioning with height, 1.10 meters, concrete quality (fc) 40 MPa, consisting of 2 tendons used type VSL type 12 with as many as 10 strand cables and other buildings using concrete regular boned).Dalam perencanaan Jembatan Cumpleng di Kecamatan Slahung Kabupaten Ponorogo dengan bentang keseluruhan 30 meter, lebar keseluruhan jembatan 4,20 meter dan lebar perkerasan 3,50 meter. Mengingat Jembatan Cumpleng merupakan salah satu dari beberapa jembatan yang ada di lingkungan proyek pengembangan wilayah Kecamatan Slahung. Jembatan ini mempunyai arti yang penting sebagai penghubung antara Desa Slahung dan Desa Galak, sehingga diharapkan dapat memperlancar arus lalu lintas serta meningkatkan perkembangan perekonomian dan pembangunan di daerah. Pada studi perencanaan ini kami menggunakan metode pratekan untuk menghitung perhitungan sandaran dan tiang sandaran, lantai kendaraan, gelagar induk dan abutment/bangunan bawah. Hasil dari perencanaan jembatan ini meliputi : perencanaan tiang sandaran, lantai kendaraan, balok induk dan balok melintang. Balok induk menggunakan beton pratekan komposit metode pasca tarik (post-tensioning dengan tinggi, 1,10 meter, mutu beton (fc) 40 Mpa, terdiri 2 buah tendon dipakai jenis VSL tipe 12 dengan kabel untaian sebanyak 10 buah dan bangunan yang lain menggunakan beton bertulang biasa).